Mapping Subnational Poverty in Zambia - de la Fuente, Alejandro; Murr, Andreas; Rascón, Ericka (World Bank, Washington, DC, 2015)
Many challenges were identified during the Fifth National Development Plan (FNDP) in Zambia. To address these challenges and realize pro-poor growth, the Sixth National Development Plan (SNDP) was set in motion. The SNDP, which covers 2011 to 2015, was designed to accomplish three goals: to accelerate infrastructure development (roads, bridges, air, water, rail and border infrastructure, feeder roads, water canals, tourist access roads), to improve the provision of basic services including water and sanitation, electricity access, health, education and skills development to promote rural investment; and to accelerate poverty reduction, mainly through the continued implementation of the Rural Finance Program and to enhance human development.